Risk: a new device for social arbitration - Mitjavila, Myriam (Tempo Social, 2002)
In the last two decades, social sciences have been registering and analyzing the growing appearance of a new way to codify the dangers and threats that characterize social life in contemporary societies. This consists of the proliferation of discourses and technical/ political practices organized in function of risk. We can observe that there exists consensus in the sociological literature about the definition of risk as social construction and the complex relationships between risk and scientific - technical knowledge. This work especially discusses the socio - technical and institutional bases of risk as a device for arbitrage of social problems in such diverse levels as the selective provision of social services, determination of guilt and/or danger in criminal behavior, allowance of credits in the financial system, management of human resources in the labor area, and others.